Gender, sex and children's play - Kilvington, Jacky; Wood, Ali (Bloomsbury Academic, 2016)
"Does gender, sex and sexuality influence children's play, and their learning? Can/should professionals try to influence children's gender and sexual concepts? Can/should professionals try to prevent gender stereotyping? These and other questions are explored in a lively and thought-provoking text that looks at why and how children inhabit or develop their gender and sexuality. Written in an approachable way and illustrated with case studies and linked to current research and theory, the book helps students, teachers and playworkers understand the debates about biology versus culture and social learning and how these impact on children's expression of gender and sexuality. Engaging the reader in a thorough reflection of their own views and approaches to the genderized and sexualized behaviour of children at play, this text is an invaluable guide for all those interested in the importance of play, gender and sexuality and how they relate to children's lives. Topics include: play and the behaviour of boys and girls within particular social contexts; play and girls' and boys' sexual behaviour and their associated feelings; play and children's self-concepts and expectations; the professional adult workers' role and the manifestation of genderized and/or sexualized play behaviour both in and outside a setting."--Provided by publisher.